Analisa Pengaruh Kualitas Produk Terhadap Kepuasan Konsumen Menggunakan Metode Kuantitatif Pada CV. Meubele Berkah Tangerang - Imron, Imron (Indonesian Journal on Software Engineering (IJSE), 2019)
Abstract: The large number of new companies offering a variety of similar products at lower prices raises intense competition to increase sales. Therefore, improving product quality is something that must be done in order to attract potential customers and increase the number of purchases. Based on the type of data obtained by the authors in this study, the authors used a quantitative method using descriptive research methods to describe the results of research conducted. In this study the authors used a questionnaire as a tool to collect data. Then the data obtained were analyzed using validity test, reliability test, normality test, heteroskedacity test, simple linear regression analysis, t test (partial) and determinant test with the help of SPSS version 25. From the results of the analysis carried out by researchers it can be concluded that there is a quality effect product to customer satisfaction on CV. Meubele Berkah Tangerang, this means H0 is rejected and H1 is accepted. Keywords: Quantitative, SPSS, Product Quality, Consumer Satisfaction